Judi Leklean di Desa Pudun Jae di Tinjau Hukum Pidana Islam - Siregar, Zulfadly; Nasution, Muhammad Arsad; Sainul, Ahmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This study examines Leklean gambling in Pudun Jae Village in Review according to Islamic Criminal Law. The type of this research is qualitative or field research and the primary data source is data or information obtained directly through interviews with the people of Pudun Jae Village who carry out Leklean activities including statements from various parties, namely, Village Heads, Traditional Leaders, Ulama, Community, Card Player and Host. The secondary data sources are books, journals and documents that are considered related to this paper, while the data collection techniques are by means of observation, interviews and documentation and then the data analysis technique is qualitative descriptive. The results of this study explain that the implementation of Leklean is a community activity that is present on the night before the celebration event is carried out with many various activities such as preparing for tomorrow's needs, telling stories, keeping the location and playing cards. The factor that makes Leklean activities still exist today is that Leklean activities are very helpful to people who are doing events because if there is a Leklean then the location of the event will be safe from thieves and people who want to interfere with the event. The review of Islamic Criminal Law regarding Leklean is to explain that in Leklean Activities at the Sukur event, there is a card game that uses money as a bet so that the game feels enthusiastic. There are elements of gambling, elements of gambling in Islamic Criminal Law, namely the existence of games and bets, which causes a party to win and a party to lose. Islam forbids its people to seek and collect wealth in a vanity way such as gambling. Because the harm that exists in playing gambling is greater than the benefits.